2015
DOI: 10.1017/s1041610215000927
|View full text |Cite
|
Sign up to set email alerts
|

Dementia care mapping: effects on residents’ quality of life and challenging behavior in German nursing homes. A quasi-experimental trial

Abstract: DCM exhibited no statistically significant effect in terms of QoL and challenging behavior of PwD in NHs. To increase the likelihood of a positive effect for PwD, it is necessary to ensure successful implementation of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
77
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 31 publications
4
77
0
1
Order By: Relevance
“…The average age and the proportion of males/females are comparable to other studies performed in LTCF [2,18]. Moreover, the QUALIDEM scores were also similar to those in other studies on persons with dementia [18,57,58]. …”
Section: Discussionsupporting
confidence: 86%
“…The average age and the proportion of males/females are comparable to other studies performed in LTCF [2,18]. Moreover, the QUALIDEM scores were also similar to those in other studies on persons with dementia [18,57,58]. …”
Section: Discussionsupporting
confidence: 86%
“…low power, no random allocation of clusters, the challenge of measuring the QoL of PwD), the unexpected and nonsignificant negative trend of the primary outcome, QoL, in both groups using DCM (Dichter et al . ) is likely coincidental. However, we did not specifically focus on explanations for this negative trend in our process evaluation because we did not expect it.…”
Section: Discussionmentioning
confidence: 96%
“…This trial failed to demonstrate a significant effect of the DCM method on the quality of life (QoL) or challenging behaviour of PwD (Dichter et al . ). Instead, examining DCM between baseline (T0) and the 18‐month follow‐up (T2), this trial showed an unexpected and nonsignificant negative trend in the primary outcome (QoL) for both included groups.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies of DCM in nursing home settings reported difficulties similar to ours in fulfilling the DCM-preconditions. These studies concluded that to reach optimal effect of DCM, the implementation requires strong and accurate attention (Brownie & Nancarrow, 2013;Chenoweth et al, 2015;Dichter et al, 2015;Jaycock et al, 2006;Jeon et al, 2012;Quasdorf et al, 2017;Rokstad, Vatne, Engedal, & Selbaek, 2015;Van de Ven, 2014). Increasing the number of realized preconditions is likely to increase the success of the implementation (Chenoweth et al, 2015;Rokstad et al, 2015;Van de Ven et al, 2013).…”
Section: Discussionmentioning
confidence: 99%